the distributive property....u r basically multiplying the number outside of the parenthesis by everything inside the parenthesis...this gets rid of the parenthesis.
3(-4x + 8)...distribute the 3 thru the parenthesis
(3 * -4x) + (3 * 8) ...take that 3 and multiply it by every number in the parenthesis..to get rid of the parenthesis
-12x + 24 <===
4(x - 6y) =
(4 * x) - (4 * 6y) =
4x - 24y <===
6(5 - q) =
(6 * 5) - (6 * q) =
30 - 6q <===
1/2(c - 8) =
(1/2 * c) - (1/2 * 8) =
1/2c - 4 <===
-3(5 - b) =
(-3 * 5) - (-3 * b) =
-15 - (-3b) =
-15 + 3b <===
(d + 2)(-7)....re-arrange
-7(d + 2) =
(-7 * d) + (-7 * 2) =
-7d + (-14) =
-7d - 14 <===